Use Of Information Technology In Rural Development” (International Journal of Engineering and Computer Science, 2013)
A rural development programmed aims at three things: economic development of the village community; restoration of ecological balance in the village; and improvement of economic and social conditions of the resource poor and disadvantaged sections of the village community through access to income generating opportunities. The speed of technological developments in the fields of communication has no doubt changed the face of media and society in the past two to three decades. These developments are so fast that the social scientists and researchers are finding it difficult to asses, assimilate understand and interpret their impact on different communities and social groups. The development of the Internet and multimedia applications has given a new impetus to the external communication of economic and social agents. Not only are businesses and public authorities concerned, but also the not-for-profit, educational and cultural world as well. The step by step procedure for developing a rural area in terms of technology is to be defined.